2019
DOI: 10.25165/j.ijabe.20191202.2834
|View full text |Cite
|
Sign up to set email alerts
|

Simulation-based optimization of control policy on multi-echelon inventory system for fresh agricultural products

Abstract: As fresh agricultural products are perishable and vulnerable, reducing inventory cost is a strategic target for supply chain enterprises. How to design a reliable multi-echelon inventory control policy is still a great challenge. Therefore, the inventory cost of a three-level fresh agricultural products inventory system was firstly mathematically analyzed. Then, the simulation-based optimization model of the multi-echelon inventory system for fresh agricultural products was proposed by using the Flexsim simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Combined the simulation and optimization method for multi-echelon inventory system studies are found in (Xu, Feng, Chen , Wang, & Wang, 2019), (Kochel & Nielander, 2005), (Duan & Liao, 2014). The inventory analysis comprises of three phases.…”
Section: Methodsmentioning
confidence: 99%
“…Combined the simulation and optimization method for multi-echelon inventory system studies are found in (Xu, Feng, Chen , Wang, & Wang, 2019), (Kochel & Nielander, 2005), (Duan & Liao, 2014). The inventory analysis comprises of three phases.…”
Section: Methodsmentioning
confidence: 99%
“…The order strategy of supply chain within one month (T = 30 days) is planned. The data were obtained from reference [36] of data category combining marketing studies. Table 3.…”
Section: Decentralized Strategymentioning
confidence: 99%
“…In addition, a few studies hold that the supply chain efficiency can be improved by tailoring supply chain for FAPs or adopting new production and marketing mode (He et al [7] and Jonkman et al [8]). Xu studied the inventory cost of a three-level FAPs inventory system [32].…”
Section: Different Contract Coordination Mechanismsmentioning
confidence: 99%